The handbook of community safety, gender and violence prevention: practical planning tools - Whitzman, Carolyn (Earthscan, 2008)
Introduction to the issues -- What this book is, and is not -- Challenging the traditional crime and punishment approach -- Box 1: What are high income and low income countries? -- Developing a new framework for community safety and violence prevention -- Brief outline of the rest of the book -- Defining the problem: the prevalence of violence and insecurity -- Defining community safety and violence -- Box 2: Violence: a lexicon -- The prevalence of violence: an overview -- Box 3. Violence versus crime -- Violence across the life course: -- Childhood 0-14 -- Youth and young adulthood 15-29 -- Adulthood 30-59 -- Old age 60 plus -- Violence and insecurity -- Box 4. A short note on "race" and violence -- Summary: a largely private issue or a public concern? -- Box 5. Violence in a global city: a thought experiment -- Analysing the problem: causes, impacts, and prevention of violence -- Root causes of violence/ risk and resilience factors -- The costs of violence -- The prevention of violence -- Conclusion: from analysis to action on violence prevention -- Coordinated community safety: from local to global -- Coordination and the question of scales -- Box 6. Environmental determinants of health -- Coordination at the neighbourhood scale -- Box 7. Neighbourhood capacity building in Buenos Aires -- Box 8. Reducing crime and violence in a Danish housing estate -- Coordination at the city scale -- Box 9. Community safety begins at home: coordinated intimate partner abuse prevention in Duluth US and London UK